Acid buffering effects of aqueous leaf extract of Ocimum gratissimum L. in the rabbit stomach - Spencer NWANGWU; Kazeem AJEIGBE; Dayo OMOTOSO; Sunday JOSIAH; Ayodeji OLAYANJU; Ayodeji BOLAJI (Turkish Journal of Gastroenterology, 2019)
-